2021
DOI: 10.1002/eng2.12422
|View full text |Cite
|
Sign up to set email alerts
|

Production of biolubricant samples from palm kernel oil using different chemical modification approaches

Abstract: This work focused on the chemical synthesis and characterization of palm kernel oil (PKO) for biolubricant production using transesterification of palm kernel methyl ester with trimethylolpropane (TMP) and epoxidation‐esterification methods. The PKO was extracted using solvent extraction method. The physicochemical characteristics of the PKO and produced biolubricant samples were determined using standard methods. Fourier transform infrared (FTIR) spectrometry and gas chromatographic (GC) analyses were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Unsaturated bonds undergo oxidation to form epoxy groups, commonly known as oxirane rings. During this process epoxides are formed when double bonds react with peracids [4] . This is accomplished by a coordinated process that results in cis stereospecific addition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated bonds undergo oxidation to form epoxy groups, commonly known as oxirane rings. During this process epoxides are formed when double bonds react with peracids [4] . This is accomplished by a coordinated process that results in cis stereospecific addition.…”
Section: Introductionmentioning
confidence: 99%
“…During this process epoxides are formed when double bonds react with peracids. [4] This is accomplished by a coordinated process that results in cis stereospecific addition. A cis olefin produces a cis epoxide, while a trans olefin produces a trans epoxide.…”
Section: Introductionmentioning
confidence: 99%
“…In many study domains, the quantity of research focusing on these transversal subjects is increasing at an exponential rate. Because both fossil fuels and oils generated by plants were once plants countless years ago, it seems logical that they're chemically similar [2] [3]. Today, epoxidized vegetable oil is becoming increasingly popular because it is utilised to replace petroleum-derived sources [4].…”
Section: Introductionmentioning
confidence: 99%
“…New and sustainable lubricants are also needed to replace conventional lubricants derived from fossil fuels. This could solve many recent environmentally‐related challenges and will resolve issues concerning their sustainability 2,3,4 . With additional problems surrounding climate change on the global scale, and exhaustion of oil reserves rising, the need for several environmentally friendly and sustainable options compared with current practices continues to gain maximum focus and attention 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This could solve many recent environmentally-related challenges and will resolve issues concerning their sustainability. 2,3,4 With additional problems surrounding climate change on the global scale, and exhaustion of oil reserves rising, the need for several environmentally friendly and sustainable options compared with current practices continues to gain maximum focus and attention. 5 For instance, in Europe, yearly, research has shown that 20% of the 5.2 million tonnes of lubricant used is discharged into the ecosystem, and 1 kg of said mineral oil has the potency to contaminate large and significant volumes of water.…”
Section: Introductionmentioning
confidence: 99%